Ação docente em um Centro Universitário: limites e possibilidades - Corrêa, José Luiz Falotico (2011)
This paper aims to collect data through a qualitative research, in order to discuss the teacher action at a University Center. This investigation involved bibliographical, documental and field research. The field research was based on questionnaires distributed, an interview with a teacher from the IES (Institute of Higher Education) and interviews with coordinators, using the focus group technique. The scenery for our study and analysis was a University Center in the interior of the State of São Paulo, and we focused on the actions of teachers in graduation courses, concerning their pedagogical stances, objectives, beliefs and formations. Finally, we tried to analyze the limitations found throughout this path and the possibilities that can be identified for the teacher action. By verifying such aspects, we tried to establish the relation of this fact with the teacher action in the classroom. All of this without losing sight of the teacher formation, its proposals, targets and profile. Believing that the teacher formation is done in a continuing process that aggregates personal formation to an initial formation which, added to the continuing education in practice, creates a professional which is in constant qualification in the eagerness of improving as an expert teacher who is aware of his/her social, scientific and political roles, which are of extreme importance to society. Our aims induce us to propose a Teacher Education Program with institutional support, which aims to better prepare teachers for their activity